2013
DOI: 10.1155/2013/181820
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and Specific Absorption Rate Studies of Ball-Milled Iron Oxide Nanoparticles for Biomedicine

Abstract: Comparative studies are presented of iron oxide nanoparticles in the 7-15 nm average diameter range ball milled in hexane in the presence of oleic acid. Transmission electron microscopy identified spherical particles of decreasing size as milling time and/or surfactant concentration increased. Micromagnetic characterization via Mössbauer spectroscopy at room temperature yielded broadened magnetic spectroscopic signatures, while macromagnetic characterization via vibrating sample magnetometry of 7-8 nm diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Thus, Néel relaxation of a small fraction of the iron particles is probably the main active mechanism. Despite the small SAR values, the heating rate is similar to several results found in the literature [20,21].…”
Section: Heat Releasesupporting
confidence: 88%
“…Thus, Néel relaxation of a small fraction of the iron particles is probably the main active mechanism. Despite the small SAR values, the heating rate is similar to several results found in the literature [20,21].…”
Section: Heat Releasesupporting
confidence: 88%
“…According to the result, it was evident that all of the as-prepared nanostructures show sharp absorption peaks in the range of 520–610 cm –1 known for the iron oxide Fe–O stretching backbone vibrations at tetrahedral sites. 32 Nevertheless, it is also noticed that the peak was shifted to shorter wavenumbers as the SPN was surface functionalized. FTIR spectra revealed that the Fe–O peak for bare SPN was observed at 543.88 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of Figure 4.6 show a comparison of the IONPs/OA, IONPs/OA/AN/PVA, and AN in the wavenumber ranging from 4000 cm -1 to 500 cm -1 . The observed spectrum of IONPs/OA agrees with those previously published by various researchers [169,[174][175][176]. The analysis of IONPs/OA and IONPs/OA/AN/PVA indicates absorption peaks at 580 cm -1 , corresponding to the Fe-O vibration related to the magnetite phase [71].…”
Section: Ftir Spectroscopy and Tgasupporting
confidence: 89%